ChemInform Abstract: Novel Synthesis of Angular Thiazolo[5, 4‐f] and [4, 5‐h]Quinazolines, Preparation of Their Linear Thiazolo[4, 5‐g] and [5, 4‐g]Quinazoline Analogues. Issue 33 (25th July 2013) - Hedou, Damien; Guillon, Remi; Lecointe, Charlotte; Loge, Cedric; Chosson, Elizabeth; Besson, Thierry
Abstract Compound (XI) is synthesized via established reactions as shown in the scheme.